THE ONEIRISTIC AND HALLUCINATORY-PARANOID DIFFUSION IN «SATTELITES» BY ANDRIY ZHURAKIVSKYY - Стрільчик, Б. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article considers the work "Satelites" by Andriy Zhurakivskyy as an object for sociocultural and phsychoanalitical analysis. It finds the main types of uncondiciousness, forms. The oneiric structure and reveals certain fragments in ideological and mass cultural discourse.